Characterisation of Pasteurella multocida isolated from rabbits in the Czech Republic - Z. Jaglic; Z. Kucerova; K. Nedbalcova; P. Kulich; P. Alexa (Veterinární Medicína, 2006)
Twenty seven Pasteurella multocida rabbit isolates were characterised by pulsed-field gel electrophoresis (PFGE) generated by restriction endonuclease ApaI, and examined for the presence of capsule and fimbriae, and tested of haemolytic activity and endotoxin release in presence of rabbit plasma. Among the isolates a high number (n = 20) of different PFGE types was observed. All isolates were found to be encapsulated and four of them also possessed fimbriae. Although the presence of the aphA gene, conferring a haemolytic phenotype for Escherichia coli under anaerobic conditions, was indicated in all of the isolates by PCR, clear haemolytic activity was observed in only one isolate when grown anaerobically. All of the isolates grew easily in the presence of rabbit plasma which showed a high capacity to bind the released endotoxin.